2006
DOI: 10.1162/jocn.2006.18.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Orienting Attention to Points in Time Improves Stimulus Processing Both within and across Modalities

Abstract: Spatial attention affects the processing of stimuli of both a task-relevant and a task-irrelevant modality. The present study investigated if similar cross-modal effects exist when attention is oriented to a point in time. Short (600 msec) and long (1,200 msec) empty intervals, marked by a tactile onset and an auditory or a tactile offset marker, were presented. In each block, the participants had to attend one interval and one modality. Event-related potentials (ERPs) to auditory and tactile offset markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
85
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 70 publications
15
85
3
2
Order By: Relevance
“…The latency of these effects is similar to what was reported previously for auditory stimuli (100-140 msec in Lange & Röder, 2006;Lange et al, 2003) and for the interaction of temporal and spatial expectancies on visual processing (110-130 msec in Doherty, Rao, Mesulam, & Nobre, 2005). These effects also fall into the same range as typical auditory spatially selective attention effects in studies with a similar design (e.g., Hansen & Hillyard, 1980;Hillyard et al, 1973;Hillyard, Woldorff, Mangun, & Hansen, 1987;Näätänen, Teder-Sälejärvi, Alho, & Lavikainen, 1992), suggesting that both spatial and temporal selection criteria can be applied at the same level of auditory processing.…”
Section: Fixationsupporting
confidence: 89%
See 2 more Smart Citations
“…The latency of these effects is similar to what was reported previously for auditory stimuli (100-140 msec in Lange & Röder, 2006;Lange et al, 2003) and for the interaction of temporal and spatial expectancies on visual processing (110-130 msec in Doherty, Rao, Mesulam, & Nobre, 2005). These effects also fall into the same range as typical auditory spatially selective attention effects in studies with a similar design (e.g., Hansen & Hillyard, 1980;Hillyard et al, 1973;Hillyard, Woldorff, Mangun, & Hansen, 1987;Näätänen, Teder-Sälejärvi, Alho, & Lavikainen, 1992), suggesting that both spatial and temporal selection criteria can be applied at the same level of auditory processing.…”
Section: Fixationsupporting
confidence: 89%
“…One example of this distinction has been reported for visual spatial processing; early visual perception sometimes reflects coarse spatial selection, such that all images presented in the same quadrant as a cued location elicit a larger visual P1, whereas only images presented very near cued locations elicit a larger amplitude N2 (Bush, Sanders, & Cave, 2007;Eimer, 1999;Kasai, Morotomi, Katayama, & Kumada, 2003;Shedden & Nordgaard, 2001). Previous studies of temporally selective attention that have reported effects on early perceptual processing Griffin et al, 2002, Experiment 1;Lange & Röder, 2006;Lange et al, 2003) have not distinguished between extremely coarse selection (anything presented before a temporal boundary, rather than anything presented after) and precise temporal selection. In the present article, if early selection had been acting in a before-or-after manner, ERPs elicited by sounds presented at 1,000 msec when listeners were attending to that interval would have been similar to those presented when listeners were attending to the short or to the long interval.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, the participants would have had no strategic reason to direct their attention to a particular point in the stimulus stream in advance. Previous research has shown that target discrimination performance can improve when targets appear at an expected point in time as compared with when they appear at an unexpected point in time (see, e.g., Correa, Sanabria, Spence, Tudela, & Lupiáñez, 2006;Lange & Röder, 2006;Nobre, 2001). Indeed, the fact that performance in Experiment 1 improved when the audiovisual target stimuli were presented at the end of the distractor stream, as compared with when they appeared at the two middle positions, may reflect the fact that participants, after having been presented with three synchronous distractors beforehand, were able to infer that the target would be in the last position and thus direct their attention temporally (Barnes & Jones, 2000;Riess-Jones, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of early cortical evoked potentials, such as the N1 component, has been shown to be associated with attentional enhancement of early sensory selection of auditory inputs from the attended locations or channels (e.g., Hansen & Hillyard, 1980;Hillyard et al, 1973) or inputs that appeared in the attended temporal intervals (e.g., Astheimer & Sanders, 2009;Lange et al, 2003;Lange & Röder,. 2006;Sanders & Astheimer, 2008).…”
Section: Genetic Correlates Of Cortical Evoked Potentialsmentioning
confidence: 99%